2006
DOI: 10.1074/jbc.m512097200
|View full text |Cite
|
Sign up to set email alerts
|

MarA-mediated Transcriptional Repression of the rob Promoter

Abstract: The Escherichia coli transcriptional regulator MarA affects functions that include antibiotic resistance, persistence, and survival. MarA functions as an activator or repressor of transcription utilizing similar degenerate DNA sequences (marboxes) with three different binding site configurations with respect to the RNA polymerase-binding sites. We demonstrate that MarA down-regulates rob transcripts both in vivo and in vitro via a MarA-binding site within the rob promoter that is positioned between the ؊10 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 44 publications
7
40
0
Order By: Relevance
“…The regulation of the acrAB genes has been studied extensively in human-pathogenic enterobacteria. Several members of the AraC/XylS family, including MarA, RamA, Rob, and SoxS, have been identified as positive transcriptional regulators of this efflux system (10,13,14,21,54,58). In this study, we identified four regulators from the plant pathogen E. amylovora that are closely related to the MarA/Rob/ SoxS group of AraC/XylS transcriptional activators from E. coli (see Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The regulation of the acrAB genes has been studied extensively in human-pathogenic enterobacteria. Several members of the AraC/XylS family, including MarA, RamA, Rob, and SoxS, have been identified as positive transcriptional regulators of this efflux system (10,13,14,21,54,58). In this study, we identified four regulators from the plant pathogen E. amylovora that are closely related to the MarA/Rob/ SoxS group of AraC/XylS transcriptional activators from E. coli (see Fig.…”
Section: Discussionmentioning
confidence: 91%
“…These data suggest that soxS plays a greater role than marA in MDR in 104-cip. Expression of marA decreased following deletion of soxS and vice versa, highlighting the cross-regulation that exists between these transcriptional factors (12,43). Recently, ramA has been reported to contribute to fluoroquinolone resistance and MDR in serovar Typhimurium through activation of acrB (1).…”
Section: Discussionmentioning
confidence: 99%
“…As overexpression of rob has been shown to confer MDR in E. coli through activation of acrB (46), it is reasonable to assume a lack of involvement of this regulator in the development of MDR in this study. The decreased expression of rob in 104-cip is likely due to downregulation by soxS and marA (28,43). The nature and extent of the cross talk between ramA and other global regulators are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the MexR protein isolated from Pseudomonas aeruginosa is a repressor of the MexAB-OprM operon, which encodes a tripartite multidrug efflux system (1). In general, the mar loci mediate a global stress response involving a large network of genes (3,39,51), and the same operon contributes to ethanol tolerance in engineered ethanologenic E. coli cells (28).…”
mentioning
confidence: 99%